Src-homology domain 2 containing protein tyrosine phosphatase-1 (SHP-1) directly binds to proto-oncogene tyrosine-protein kinase Src (c-Src) and promotes the transcriptional activation of connexin 43 (Cx43). Issue 5 (2nd May 2022) - Liu, YiHao; Dai, Meng; Yang, PengHui; Cao, Li; Lu, Li
ABSTRACT: The prevalence of atrial fibrillation (AF), which is one of the common arrhythmias in clinics, is increasing sharply and has affected millions of patients, which is expected to triple by 2050. The purpose of the study was to explore the regulatory relationship between Src-homology domain 2 containing protein tyrosine phosphatase-1 (SHP-1) and proto-oncogene tyrosine-protein kinase Src (c-Src) and the regulation of Connexins 43 (Cx43), and its effect on AF was also studied. Mouse atrial myocyte line (HL-1 cell line) was used as the research object. After overexpression of SHP-1, the expressions of p-c-Src, Cx43, and SHP-1 were detected by Western blot and cellular immunofluorescence, respectively. The location and interaction of SHP-1 and c-Src in the cells were detected by immunofluorescence co-localization and co-immunoprecipitation (Co-IP). The regulation of c-Src and Cx43 was detected by DNA pull down, chromatin co-immunoprecipitation (CHIP), and dual-luciferase reporter system. The results revealed that overexpression of SHP-1 could inhibit the phosphorylation and activation of c-Src and increase the expression of Cx43. Moreover, there was a direct binding between SHP-1 and c-Src, and c-Src could bind to the promoter region of Cx43 and inhibit the transcription of Cx43. In conclusion, SHP-1 could bind to c-Src and inhibit the activity of c-Src, thus enhancing the transcriptional activation of Cx43 and improving the function of gap junction. Graphical abstract: uf0001